The role of background music in the experience of watching YouTube videos about death and dying - Pentaris, Panagiotis; Yerosimou, Maria (Journal of Education Culture and Society, 2020)
YouTube is the largest video sharing site live at the moment. It has been used to communicate a vast array of information, while it allows for user-generated content. This paper will focus on YouTube videos that communicate death, and in particular will present findings from a preliminary study undertaken by the authors considering the role that background music plays in these videos.Specifically, this study explores the experiences of the viewers of death-related YouTube videos with and without background music while it makes comparisons in relation to the impact that music has on the viewers’ emotional experiences.We conclude that background music elicits emotions and enhances feelings of sadness and sympathy in relation to the visual content of videos while recommendations for future research are made.